Evaluation Of Bolu Menara Sales Data With The C.45 Algorithm Using The Rapid Miner Application - Rajagukguk, Denni M.; Panjaitan, Muhammad Iqbal (Sean Institute, 2023)
In recent years, the cake and pastry market, including Bolu Menara, has grown rapidly and attracted many customers. This research looks at Bolu Menara sales data collected during a certain period using the C.45 algorithm from the RapidMiner application. The aim of this method is to discover purchasing patterns and understand consumer patterns to improve marketing strategies. For example, the analysis results show that consumers with certain criteria tend to buy Bolu Menara more often than other people. So, this method succeeds in finding sales patterns that can be used as a basis for marketing strategies, enabling businesses to improve their marketing efficiency and effectiveness.